Homogeneous Structures and Homogeneous Geodesics of the Hyperbolic Oscillator Group - Giovanni Calvaruso; Amirhesam Zaeim; Mehdi Jafari; Moslem Baghgoli (Axioms)
In this paper, we study some homogeneity properties of a semi-direct extension of the Heisenberg group, known in literature as the hyperbolic oscillator (or Boidol) group, equipped with the left-invariant metrics corresponding to the ones of the oscillator group. We identify the naturally reductive case by the existence of the corresponding special homogeneous structures. For the cases where these special homogeneous structures do not exist, we exhibit a complete description of the homogeneous geodesics.